FILSAFAT PENDIDIKAN SEBAGAI LANDASAN PEMBENTUKAN KARAKTER PADA GENERASI Z DI ERA DIGITAL - Nurwandayani; Irawati; Fatimah Azis; Kaharuddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The advancement of the digital age has undoubtedly brought about significant changes in various aspects of life, including education. However, challenges that must be faced, arising concurrently with technological development, require the formation of a resilient educational character to withstand negative impacts and optimize its positive benefits for Generation Z. The purpose of this study is to analyze how philosophy serves as the foundation for character formation for Generation Z in the digital age. It is important to recognize that philosophical values ​​function not only as theory but also as ethical and reflective guidelines. The research method used for this study was qualitative, using a literature study approach, collecting and analyzing various academic sources on the function of philosophy of science and the challenges of education in the digital age. The results show that educational philosophy plays a crucial role in forming a strong and ethical educational character in the digital age. Through the application of philosophical values ​​such as critical analysis, moral introspection, and responsibility, education can create a generation prepared to face the challenges and negative effects of technological development.